Mitomycin induced pulmonary veno-occlusive disease. (2021) - Kunadu, Afua; Stalls, J. Stephen; Labuschagne, Heloise; Thayyil, Abdullah; Falls, Randall; Maddipati, Veeranna
Abstract: Pulmonary veno-occlusive disease (PVOD) is a rare but devastating cause of pulmonary hypertension (PH) characterized by preferential remodeling of the pulmonary venules. Mitomycin-C (MMC) is an alkylating agent commonly used in chemotherapy with documented lung toxicity as well as PVOD adverse effect. The incidence of PVOD in patients with anal cancer is much higher than in those with idiopathic PVOD, especially following treatment with MMC. An accurate diagnosis of PVOD can be made based on noninvasive investigations utilizing oxygen parameters, low diffusing capacity for carbon monoxide and characteristic signs on high-resolution computed tomography of the chest. No evidence-based medical therapy exists for PVOD at present and lung transplant remains the preferred definitive therapy for eligible patients. We present a case of autopsy confirmed MMC induced PVOD in a patient with metastatic anal cancer.